PENGARUH PENILAIAN PRESTASI KERJA DAN PENGEMBANGAN KARIR TERHADAP KINERJA PEGAWAI PADA BAGIAN UMUM SEKRETARIAT DAERAH KOTA SIBOLGA - Sukma Yanti Harefa; Zafril Abdi Nasution; Iqbal Batubara (CV. KAMPUS AKADEMIK PUBLISHING, 2025)
This research aims to determine whether there is an influence of work performance assessment and career development on employee performance in the General Section of the Sibolga City Regional Secretariat. The type of research used in this study is a quantitative descriptive research type, because this research method aims to obtain information by creating a picture or description of what exists or is happening. This research was conducted from April to August 2024.For this study, the population was 51 people. The population was taken from all employees of the General Section at the Sibolga City Regional Secretariat. Then, the author took the entire population to be used as a sample, namely 51 people. The type of data used in this thesis research is the type of subject data and the data source is primary.From the results of the instrument test, valid and reliable results were obtained because all questions contained in variables X1, X2 and Y have a Corrected Item-Total Correlation value, greater than 0.300 and a Cronbach's Alpha value, each variable above 0.60 which means all questions are valid. and reliability. From the classical assumption test, the research data is normally distributed because the histogram graph is bell-shaped, in the P-P Plot graph above, the data distribution can be seen close to the diagonal line and in the multicollinearity test, the tolerance value is <0.1 and the variance inflation factor (VIF) value <10, so it can be concluded that in the regression model there is a correlation between independent variables. From the results of the data test, an influence of 60.6% is obtained, this means that what happens to the variation of the dependent variable is 60.6% determined by the independent variable, from the hypothesis test, the results of the calculated t value <t table and the calculated F value> F table. Based on this, the hypothesis proposed in this study is accepted.